Subject “The development of Ukrainian language”: reinforcement of informational component (to lesson in 9 form) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article examines the problem of using linguistic studies in implementation of introductory Ukrainian lessons. Proposed materials help to elaborate skills to know difficult questions of language functioning in society. The author reorients students’ work on extended studying of special literature, discussion questions that have great importance in successful students’ and school-leavers’ socialization.
Keywords: Ukrainian language; origin theories; destruction of Ukrainian language and culture; general linguistic lessons